2002
DOI: 10.1590/s0100-39842002000400005
|View full text |Cite
|
Sign up to set email alerts
|

Classificação BI-RADS™: categorização de 4.968 mamografias

Abstract: Seguindo o modelo adotado pelo Colégio Americano de Radiologia, utilizamos o método BI-RADS™ (Breast Imaging Reporting and Data System) numa análise regional retrospectiva de 4.968 mamogramas, para categorizar e avaliar a freqüência dos achados mamográficos, distribuindo-os nos diferentes grupos desta classificação. Das 4.968 mamografias foram laudadas 44,4% (n = 2.208) como negativas, 46,3% (n = 2.305) como achados mamográficos benignos, 7,5% (n = 374) como achados mamográficos provavelmente benignos, 0,98% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
0
7
1
7
Order By: Relevance
“…More recent studies on subcategories 4A, 4B and 4C have not been found in the literature, so it has not been possible to establish a correlation with the values obtained in the present study (9)(10)(11)(12) .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…More recent studies on subcategories 4A, 4B and 4C have not been found in the literature, so it has not been possible to establish a correlation with the values obtained in the present study (9)(10)(11)(12) .…”
Section: Discussioncontrasting
confidence: 70%
“…The BI-RADS classification has represented the first attempt to standardize mammographic findings in descriptive terms, constituting an important ancillary tool in both in cases of suspect malignancy and definition of conduct to be adopted (5,(7)(8)(9) . Studies correlating mammographic and histological findings in non-palpable breast lesions employing the BI-RADS classification have found PPV for breast cancer between 12.3% and 47.8% (4,7,8,10-12) .…”
Section: Discussionmentioning
confidence: 99%
“…15 The colpocytology smear was obtained in a triple sampling, removing the scraped bottom of the vaginal sack, ectocervix, and endocervix, using an Ayres spatula and brushing the cervical collection.…”
Section: Methodsmentioning
confidence: 99%
“…However, mammography still remains as the most relevant imaging technique for breasts. In order to standardize mammographic findings reporting, the BI-RADS classification was developed, subdividing imaging findings into five classes as follows: negative, benign, probably benign, suspicious and highly suspicious of malignancy (6) .…”
Section: Discussionmentioning
confidence: 99%